2019
DOI: 10.1177/0733464819878620
|View full text |Cite
|
Sign up to set email alerts
|

Everyday Technology Use and Overall Needed Assistance to Function in the Home and Community Among Urban Older Adults

Abstract: Background: Older adults manage increasing numbers of everyday technologies to participate in home and community activities. Purpose: We investigated how assessing use of everyday technologies enhanced predictions of overall needed assistance among urban older adults. Method: We used a cross-sectional design to analyze responses from 114 participants completing the Everyday Technology Use Questionnaire, the Montreal Cognitive Assessment, and a sociodemographic questionnaire. We estimated overall needed assista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…As Walsh et al (2020) suggested, there appears to be a complex association between activity engagement and ET use for older adults, which we also believe to be true for the subset with MCI based on our findings. Participation out of home is critical for quality of life while aging in place yet are at risk for those experiencing cognitive change ( Sturge et al, 2020 ).…”
Section: Discussionsupporting
confidence: 80%
“…As Walsh et al (2020) suggested, there appears to be a complex association between activity engagement and ET use for older adults, which we also believe to be true for the subset with MCI based on our findings. Participation out of home is critical for quality of life while aging in place yet are at risk for those experiencing cognitive change ( Sturge et al, 2020 ).…”
Section: Discussionsupporting
confidence: 80%
“…The numbers of the evaluated sample were considerably varied, and the range of variation ranged from the smallest sample with six participants [ 36 ] to the largest, reaching a total population of two hundred and seventy-four individuals [ 30 ]. Most studies were conducted in Sweden ( n = 6, 55%) [ 30 , 32 , 34 , 35 , 36 , 37 ], and other studies were conducted in the United States ( n = 4, 36%) [ 28 , 29 , 31 , 38 ] and Belgium ( n = 1, 9%) [ 33 ]. For most studies, the first author was from the field of occupational therapy or occupational therapy departments from several universities ( n = 8) [ 28 , 29 , 31 , 32 , 34 , 36 , 37 , 38 ], followed by neuropsychologists or departments of psychiatry and neuropsychology ( n = 2) [ 33 , 35 ] and departments of geriatrics ( n = 1) [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Six studies used quantitative research methodologies [ 28 , 29 , 31 , 33 , 34 , 35 ], whereas four adopted qualitative research methodologies [ 32 , 36 , 37 , 38 ]. Only one study used mixed methodologies [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…This study showed that older adults begin making errors using ETs at the SMC stage, the tendency becomes more pronounced in the MCI stage, and by the AD stage, ETs become very difficult to use. It has been suggested that assessing the ability to use ETs predicts re- quirements for future support [37]. For older adults to continue living at home for as long as possible, it is important to make detailed evaluations of their abilities to use ETs in individual contexts and to provide personalized support.…”
Section: Discussionmentioning
confidence: 99%